Effect of V-Shaped Groove Microstructure on Blood Flow Resistance in Bionic Artificial Blood Vessels - Zhou Li; Yunqing Gu; Lingzhi Yu; Zhuofan Yin; Wenting Wang; Denghao Wu; Jiegang Mou; Shuihua Zheng (Applied Bionics and Biomechanics)
This study aims to investigate the blood flow in bionic artificial blood vessels and to reduce the resistance to blood flow, the drag reduction characteristics of V-shaped groove drag reduction microstructures in artificial blood vessel structures were investigated in depth. By varying the parameters of incoming flow velocity, groove width, and groove depth, the effect of various variable conditions on the drag reduction effect of the grooves was investigated, and the flow field characteristics and drag reduction effect of the V-shaped groove microstructure in the artificial blood vessel were obtained. A detailed analysis of the effect of velocity and groove size on the drag reduction effect of the groove was also carried out to demonstrate the drag reduction mechanism of the V-shaped groove microstructure and to summarize the variation law of the drag reduction rate of the V-shaped groove. The results show that the resistance reduction rate of the V-shaped groove microstructure decreases with the increase of blood flow velocity, increases with the increase of groove width, and increases and then decreases with the increase of groove depth. The velocity range used in this paper is 0.3–0.6 m/s, the groove width varies from 0 to 0.3 mm, and the groove depth varies from 0 to 0.3 mm.